The Science of Measuring Wellness. - Berne, Samuel (Journal of Behavioral Optometry, 2012)
Background: Biofield research is a new discipline emerging in medicine and science. The biofields around us are dynamic, convey information and help regulate the body's biochemistry and physiology. When we can measure the biofields, we can see the effect of compression, trauma, toxicity, and stress patterns. The biofield is a bridge between the physical body and energy field. Case Report: A six-year-old child diagnosed with Asperger's syndrome was diagnosed with convergence insufficiency following an optometric examination. Biofield testing showed the patient to be in a depleted state. Following a successful plan of vision therapy, the patient's visual deficiencies were reduced and the biofield improved. Conclusion: This case demonstrates the importance of biofield testing and the impact of vision therapy on general health and well-being.